A retrospective comparison of cognitive performance in individuals with advanced Parkinson's Disease in Hong Kong and Canada. Issue 6 (2nd November 2022) - Kwan, Vivian; Shum, David; Haffenden, Angela; Yeates, Keith Owen; Kwok, Alice; Lau, Herman; Poon, Wai Sang; Chan, Danny; Zhu, X. L.; Chan, David; Mok, Vincent; Chan, Anne; et al.
Abstract: A deeper understanding of the cross-cultural applicability of cognitive tests across countries and cultures is needed to better equip neuropsychologists for the assessment of patients from diverse backgrounds. Our study compared cognitive test scores in patients with advanced Parkinson's disease (PD) at the Prince of Wales Hospital ( n = 63; Hong Kong) and the Foothills Medical Center ( n = 20; Calgary, Canada). The groups did not differ in age or sex ( p > .05), but Western patients had significantly more years of education ( M = 14.2, SD = 2.7) than Asian patients ( M = 10.33, SD = 4.4). Cognitive tests administered to both groups included: digit span, verbal fluency (animals), the Boston Naming Test, and verbal memory (California Verbal Learning Test or Chinese Auditory Verbal Learning Test). Testing was completed before and 12 months after deep brain stimulation surgery. Results showed cognitive performance was similar across time, but significant group differences were found on digit span forward (longer among patients from Hong Kong; F (1, 75) = 44.155, p < .001) and the Boston Naming Test (higher percent spontaneous correct among patients from Canada; F (1, 62) = 7.218, p = .009, η 2 = 0.104), after controlling for age, sex, and years of education. In conclusion, our findings provide preliminary support for the similarity of Chinese versions of tests originally developed for Western populations. Also, we caution that some aspects of testing may be susceptible to cultural bias and therefore warrant attention in clinical practice and refinement in future test development for Asian patients.